"Watch out!": Effects of instructed threat and avoidance on human free‐operant approach–avoidance behavior. Issue 1 (January 2017) - Schlund, Michael W.; Treacher, Kay; Preston, Oli; Magee, Sandy K.; Richman, David M.; Brewer, Adam T.; Cameron, Gemma; Dymond, Simon
Abstract : Approach–avoidance paradigms create a competition between appetitive and aversive contingencies and are widely used in nonhuman research on anxiety. Here, we examined how instructions about threat and avoidance impact control by competing contingencies over human approach–avoidance behavior. Additionally, Experiment 1 examined the effects of threat magnitude (money loss amount) and avoidance cost (fixed ratio requirements), whereas Experiment 2 examined the effects of threat information (available, unavailable and inaccurate) on approach–avoidance. During the task, approach responding was modeled by reinforcing responding with money on a FR schedule. By performing an observing response, participants produced an escalating "threat meter". Instructions stated that the threat meter levels displayed the current probability of losing money, when in fact loss only occurred when the level reached the maximum. Instructions also stated pressing an avoidance button lowered the threat level. Overall, instructions produced cycles of approach and avoidance responding with transitions from approach to avoidance when threat was high and transitions back to approach after avoidance reduced threat. Experiment 1 revealed increasing avoidance cost, but not threat magnitude, shifted approach–avoidance transitions to higher threat levels and increased anxiety ratings, but did not influence the frequency of approach–avoidance cycles. Experiment 2 revealed when threat level information was available or absent earnings were high, but earnings decreased when inaccurate threat information was incompatible with contingencies. Our findings build on prior nonhuman and human approach–avoidance research by highlighting how instructed threat and avoidance can impact human AA behavior and self‐reported anxiety.